Effect of Sintering Temperature on AC Susceptibility and Superconducting Properties of (Bi1.6Pb0.4)Sr2CaCu2O8 Superconductor - Yusof N.M.; Bakar I.P.A.; Suib N.R.M.; Shukor R.A.; Mujaini M.; Abdullah H.; Humaidi S.; Azman N.J. (Malaysian Institute of Chemistry, 2025)
The effect of sintering on the structural and superconducting properties of the (Bi1.6Pb0.4) Sr2CaCu2O8 system has been investigated. The samples were prepared by solid-state reaction method with different sintering temperatures:820 C, 825 oC, 830 oC, 835 oC, and 840 oC. The samples were characterized by X-ray diffraction (XRD), electrical resistance, and AC susceptibility measurement. XRD patterns showed that the Bi-2212 phase with orthorhombic unit cell was found in all samples. In general, no systematic changes in lattice parameters indicating increasing sintering temperature until 840 oC did not affect the lattice. The sample sintered at 840 C showed the highest Tc-onset and Tc-zero, 84 K and 71 K, respectively. The sample with the sintering temperature of 840 C also showed the highest AC susceptibility transition temperature, Tc?? (80 K). The peak temperature of the imaginary part of the susceptibility, Tp, for the sample sintered at 840 C increased to 57 K. According to these study's findings, 840 C is the most suitable temperature for sintering (Bi1.6Pb0.4) Sr2CaCu2O8 system. ? 2024 Malaysian Institute of Chemistry. All rights reserved.